Efektifitas Undang – Undang Kepabeanan terhadap Penanggulangan Penyelundupan Sembako di Kota Batam - Hutauruk, Rufinus Hotmaulana; Susanto, Dedi (Universitas Internasional Batam, 2019)
The purpose of this research is to know the law against people in groceries Settings in Batam city is in compliance with the Customs Act, to find out the legal settlement Implementation taking action against smuggling People in Batam city. According to the law ? customs laws, to find out what factors are barriers/constraints to reduce smuggling groceries in Batam city. Data collection is carried out by the procedure and field studies libraries study authors take respondents research has to do with the issues that are discussed. As for the respondents in this study is the Head Office of the Customs and Excise unit area of Batam. The results of research that the Central Government in this case from customs and Excise in Batam city in dealing with the function of supervision. But a variety of conditions, from the geographical condition to the high consumptive society against imported goods so difficult to cooperate plus Batam port area is an area free of FTZ to vices-depravity internal irresponsible persons in the port so the practice of bribe make surveillance capacity has become weak.